Analisis Kebutuhan Guru IPS SMP di Kecamatan Wonosobo Kabupaten Tanggamus Tahun 2017 - Herli Andika Putra; Edy Haryono; Dedy Miswar (JPG (Jurnal Penelitian Geografi), 2017)
The research was purposed to assess the number of social sciences teachers needs on high school in Wonosobo Sub-districk of Tanggamus Regency in 2017. This research was used descriptive method with the population are 6 junior high school of Wonosobo Sub-district. Data collecting used observation, questionnaire, and documentation techniques. Data analyzed was used descriptive data analysis technique. The result of the research shows (1) As many as 75% of social science teachers have an appropriate educational background and 25% of social science teachers are not appropriate with their educational background. (2) The social sciences teacher needs of Wonosobo Sub-district as many as 11 teachers. (3) The number of excess social sciences teacher in SMP N 1 Wonosobo 1 teacher, SMP N 2 Wonosobo 2 teachers, and SMP Muhammadiyah 1 Wonosobo 2 teachers. (4) The Number of deficiencies social sciences teacher in SMP Muhammadiyah 2 Wonosobo 1 teacher and in SMP Muhammadiyah 3 Wonosobo 1 teacher.Penelitian ini bertujuan untuk mengkaji jumlah kebutuhan guru IPS pada SMP di Kecamatan Wonosobo Kabupaten Tanggamus Tahun 2017. Penelitian ini menggunakan metode deskriptif dengan populasi 6 SMP di Kecamatan Wonosobo. Pengumpulan data menggunakan teknik observasi, kuesioner, dan dokumentasi. Analisis data menggunakan teknik analisis data deskriptif. Hasil penelitian ini menunjukkan: (1) Sebanyak 75% guru IPS sesuai dengan latar belakang pendidikannya dan 25% guru IPS tidak sesuai dengan latar belakang pendidikannya. (2) Kebutuhan guru IPS di Kecamatan Wonosobo adalah 11 orang guru. (3) Jumlah kelebihan guru IPS di SMP N 1 Wonosobo sebanyak 1 guru, SMP N 2 Wonosobo sebanyak 2 guru, dan SMP Muhammadiyah 1 Wonosobo sebanyak 2 guru. (4) Jumlah kekurangan guru IPS di SMP Muhammadiyah 2 Wonosobo sebanyak 1 guru dan di SMP Muhammadiyah 3 Wonosobo sebanyak 1 guru.Kata kunci: guru IPS, kebutuhan, kesesuaian